2004
DOI: 10.1108/02630800410549026
|View full text |Cite
|
Sign up to set email alerts
|

Progressing the rights to light debate – Part 1: a review of current practice

Abstract: Introduces a series of articles which respond to Pitts' (2000) call for a debate into current rights to light practice. Summarises relevant areas of law as well as current measurement and valuation practices in this area. Describes the Waldram methodology, the grumble point, the fifty-fifty rule and the concept of Equivalent First Zone Loss. Shows how these concepts are used to determine the amount of damages payable where a right to light has been infringed. Calls for others to contribute to the debate propos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 2 publications
0
18
0
Order By: Relevance
“…This and related studies by Waldram also serve as the basis for the "rights to light" schema devised for the determination of daylight injury. The methodology employed by Waldram was recently critiqued in a number of papers [12] Recent studies have also shown either a preference for absolute rather than relative values, or a better correlation between user assessments of daylight adequacy and the 5/8/2016 16:22simulated occurrence of absolute values rather than the (simulated) daylight factor. In the 2012 PIER report on daylight metrics, the 300 lux indicator value represented the best correlation to occupant preference for daylight sufficiency, based on 61 spaces in California, Washington and New York, comprising 484 occupant questionnaire responses and 324 expert questionnaire responses [16].…”
Section: /8/2016 16:22mentioning
confidence: 99%
“…This and related studies by Waldram also serve as the basis for the "rights to light" schema devised for the determination of daylight injury. The methodology employed by Waldram was recently critiqued in a number of papers [12] Recent studies have also shown either a preference for absolute rather than relative values, or a better correlation between user assessments of daylight adequacy and the 5/8/2016 16:22simulated occurrence of absolute values rather than the (simulated) daylight factor. In the 2012 PIER report on daylight metrics, the 300 lux indicator value represented the best correlation to occupant preference for daylight sufficiency, based on 61 spaces in California, Washington and New York, comprising 484 occupant questionnaire responses and 324 expert questionnaire responses [16].…”
Section: /8/2016 16:22mentioning
confidence: 99%
“…Such concepts shouldn't be revolutionary, yet when they regard regulations that are slow to change, they often are. The ASL study also has implications for the UK where the almost century-old "rights to light" schema devised by Waldram [25] for the determination of daylight injury has recently been critiqued in a number of papers [26,27,28,29]. The measure of daylight used in the Waldram method is direct sky illumination under a uniform sky (without sun).…”
Section: Outcomes and Implicationsmentioning
confidence: 99%
“…The first paper (Chynoweth 2004) "grumble point"). Based on a review of archival material the current paper revisits Waldram's original arguments and re-examines some of the evidence on which they were based.…”
Section: Introductionmentioning
confidence: 99%